ANALISIS SISTEM INFORMASI PENDAFTARAN KOMPETISI ARCHERY TINGKAT NASIONAL MENGGUNAKAN ALGORITMA FIFO MELALUI METODE WATERFALL - Satrio Wibowo, Ryan Rafif; Sitorus, Michael (Infotech: Journal of Technology Information, 2025)
This research addresses the issue of inefficiency and disorder in the registration process of national-level archery competitions, which often results in data errors and unstructured participant queues. The objective of this study is to design and develop a web-based registration system capable of automatically managing participant queues, enhancing transparency, and speeding up the registration process. The methodology employed includes the application of the Waterfall software development model and the FIFO (First In First Out) algorithm for queue management. Testing results indicate that the developed system successfully performs its core functions, including input validation, automatic data management, and real-time participant listing. User surveys show a high level of acceptance regarding the system, particularly concerning fairness and transparency. The conclusion of this study is that the web-based information system developed using this approach can improve registration efficiency and transparency, with potential applicability for various sporting events.